2022
DOI: 10.1007/s10989-022-10461-7
|View full text |Cite
|
Sign up to set email alerts
|

Peptide ILE-GLU-TRP (Stemokin) Potential Adjuvant Stimulating a Balanced Immune Response

Abstract: Vaccines are widely used worldwide to prevent and protect from various infections. A variety of modern approaches to developing prophylactic and therapeutic vaccines is growing. In almost all cases, adjuvants are necessary to obtain an effective immune response.This work investigated the possibility of using the pharmaceutical peptide drug Stemokin as an adjuvant stimulating a balanced Th1/Th2 response.A study was conducted to compare the activity of Stemokin versus the approved adjuvant Alhydrogel in a murine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 38 publications
0
0
0
Order By: Relevance
“…As a result of SAR, original analogs were obtained, and based on the Ile-Glu-Trp tripeptide, the hemostimulator Stemokin was developed, acting at the level of hematopoietic stem cells [27,28]. The study of isomers and analogs of the dipeptide Glu-Trp showed that the enantiomeric peptides LL-Glu-Trp and DD-Glu-Trp exhibit a reciprocal effect on immuno-and hemoregulation at the cellular level; LL-Glu-Trp peptides have a stimulating effect, and DD-Glu-Trp peptides exhibit suppressor properties [10].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As a result of SAR, original analogs were obtained, and based on the Ile-Glu-Trp tripeptide, the hemostimulator Stemokin was developed, acting at the level of hematopoietic stem cells [27,28]. The study of isomers and analogs of the dipeptide Glu-Trp showed that the enantiomeric peptides LL-Glu-Trp and DD-Glu-Trp exhibit a reciprocal effect on immuno-and hemoregulation at the cellular level; LL-Glu-Trp peptides have a stimulating effect, and DD-Glu-Trp peptides exhibit suppressor properties [10].…”
Section: Discussionmentioning
confidence: 99%
“…In the SAR studies of synthetic Glu-Trp family peptides, the tripeptide Ile-Glu-Trp showed significant immuno-and hemostimulating effects in mice model experiments. This peptide stimulated the exogenous bone marrow colony restoration after irradiation in 1Gy and 4Gy doses, while Thymogen reduced the radiation effects only at 1 Gy [27,28]. Given the close interaction of the hematopoiesis and immune system [29] consisting of a common ancestral cell and for the regulation of specific processes of hematopoiesis by immunocompetent cells, it was of particular interest to study the possibility of using short peptides to reduce the damaging effect of ionizing radiation on hemopoiesis, particularly on the undeveloped CFU cell population [19].…”
Section: Second Generation: Stemokinmentioning
confidence: 98%